Antimicrobials Resistance Trend Of Bacterial Uropathogens in Patients Attending in Tertiary Care Hospitals In Bangladesh - Moon, Kawsar Jahan; Amin, Mohammed Ruhul; Afroj, Rumana; Alima, Foujia; Yusuf, Riti (Journal of Dhaka Medical College, 2023)
Background: Urinary tract infection (UTI) has now become the most common infectious disease, mostly in developing regions, indicating healthcare and economic constraints. Antimicrobial resistance (AMR) is a condition in which microorganisms use varied resistance mechanisms, including horizontal gene transfer (for example, plasmids and bacteriophages), genetic recombination, and mutations. Methods: This study is a retrospective cross-sectional study that was conducted at Mitford Hospital and Dhaka Medical College Hospital. The study was conducted from January 2021 to January 2022. The total sample size for this study was 500. Result: The proportion of uropathogenic species of isolates (from total UTI patients; 250) showed E. coli 94(37.6%) and followed by K. pneumoniae 28(11.2%), CONS 11(4.4%), S.aureus 23(9.2%), Proteus spp. 4(1.6%), Citrobacter Spp. 18(7.2%), Salmonella Spp. 1(0.4%), GNR 27(10.8%), Enterobacter Spp. 9(3.6%), Streptococcus spp. 6(2.4%), Klebsiella Spp. 8(3.2%), Pseudomonas Spp. 1(0.4%), Providencia spp. 1(0.4%), K.ozaenae 10(4%), Shigella Spp. 2(0.8%), Enterococcus Spp. 5(2%), Serratia spp. 1(0.4%) and M.morgani 1(0.4%). Gram-positive isolates presented a high resistance to tetracycline 14(93.3%) and penicillin 13(86.7%). Antimicrobial agents most effective against Gram-positive uropathogens were vancomycin and nitrofurantoin. Staphylococcus aureus was the most common isolate of Gram-positive isolates. It was highly resistant to tetracycline 32(100%) and trimethoprim-sulfamethoxazole 26(81.3%). In addition, 9(28.1%) of S. aureus were resistant to cefoxitin. Conclusion: UTI is the most spreading bacterial infection globally. The increase in antimicrobial resistance is associated with UTI, which is a serious threat and has become a global health emergency. J Dhaka Med Coll. 2022; 31(1) : 23-28